Reading Palestinian Resistance through Peircean Semiotics: A Semiotic and Qur’anic Analysis of Mahmoud Darwish’s Identity Card - Pratama, Rendi; Masnani, Sitti Wahidah; Mujadilah, Mujadilah; Agussalim, Andi; Ridwan, Muhammad (Faculty of Adab and Humanities - Alauddin State Islamic University of Makassar, 2025)
This study aims to analyze the poem Identity Card by Mahmoud Darwish as a representation of the identity and resistance of the Palestinian people through Charles Sanders Peirce's semiotic approach which includes icons, indexes, and symbols. The focus of the study is directed at how the meaning of suffering, attachment to the land, and the strengthening of collective identity are articulated in the poem, as well as its relationship to the Qur'anic principles of maintaining identity, defending the homeland, and resisting oppression. The research method used is qualitative-descriptive with Peirce's semiotic approach. Primary data is in the form of the text of the poem Identity Card, while secondary data is obtained from scientific literature on the life of Mahmoud Darwish, the context of the Palestinian struggle, as well as the study of interpretation and hadith related to the value of resistance. An analysis of the nine main quotes of the poem was carried out using the Peirce framework, then enriched with a normative-religious perspective to reveal the ethical and spiritual dimensions of the resistance presented. The results of the study show that the icon depicts the concrete reality of the suffering of the Palestinian people due to occupation; the index reflects an existential attachment to the land understood as a divine trust; Meanwhile, symbols contain collective resistance through diction such as